Diiron hexacarbonyl complexes bearing naphthalene-1, 8-dithiolate bridge moiety as mimics of the sub-unit of [FeFe]-hydrogenase: synthesis, characterisation and electrochemical investigations. (15th October 2015) - Qian, Guifen; Zhong, Wei; Wei, Zhenhong; Wang, Hailong; Xiao, Zhiyin; Long, Li; Liu, Xiaoming
Abstract : Reducing the formyl group into a hydroxyl group allows the further synthesis of novel diiron complexes with various functionalities. Abstract : Eight diiron hexacarbonyl complexes bearing a 1, 8-dithionaphthalenyl bridging linkage as mimics of the diiron subunit of [FeFe]-hydrogenase are reported. Reaction of Fe3 (CO)12 with naphtha[1, 8- cd ][1, 2]dithiole- n -carbaldehyde ( n = 2:2a or 4:2b ) gave two complexes, [Fe2 (μ-S)2 R(CO)6 ] (–SRS– = n -formylnaphthalene-1, 8-bis(thiolate), n = 2:3a, 4:3b ), which were further used as precursors to prepare six other complexes by manipulating the formyl groups. Converting the corresponding formyl group into a hydroxymethyl group (CH2 OH) led to complexes4a and4b . Their reactions with halobutanoyl chloride formed complexes5a and5b (halo group = Cl), and6a and6b (halo group = Br), respectively. Among the complexes, 3a, 3b, 4b, 5b, and6a were crystallographically analysed. Electrochemical investigations into these complexes revealed that the formyl group exerts profound electronic influence on the electrochemistry, and thus catalysis of proton reduction, due to its involvement in the conjugation of the bridging linkage. DFT calculations indicate that the formyl group influences the electrochemistry and catalysis by significantly altering the composition of the LUMOs.